Enzymology in drug discovery 2 - Copeland, Robert (Henry Stewart Talks, 2013)
Enzymes as targets for drug discovery, Protein-ligand binding equilibria, Enzyme reaction mechanisms, Structure and function of enzyme active sites, Measuring enzyme velocity in the laboratory, Reversible modes of enzyme inhibition, Enzyme inhibition as a mechanism of pharmacological intervention in disease, Clinical value of different inhibition modalities, Non-classical inhibition, Enzyme assays and screening criteria, Lead optimization, Summary: basic information to look for